2019
DOI: 10.1002/mnfr.201900550
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NLRP3 Inflammasome in Neuroinflammation: Health Promoting Effects of Dietary Phytochemicals in Neurological Disorders

Abstract: Neurological disorders occur in the central and peripheral nervous system and include Alzheimer's disease, stroke, and spinal cord injury. Activation of the innate immune system inevitably occurs in all forms of neurological disorders. The NOD‐, LRR‐ and pyrin domain‐containing 3 (NLRP3) inflammasome is a multimolecular complex that can sense danger signals associated with neurological disorders. Assembly of the NLRP3 inflammasome promotes caspase‐1‐mediated interleukin‐1β and interleukin‐18 maturation in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 177 publications
0
37
0
Order By: Relevance
“…Activated microglia can produce cytokines and chemokines that induce astrogliosis, which is a hallmark of neuroinflammation. [ 17 ] Consequently, the proinflammatory mediators could induce a vicious inflammatory cycle, causing neuronal cell dysfunction and death in the brain constantly. [ 18,19 ] Meanwhile, in the central nervous system (CNS), inflammation occurring and progressing can be mediated via activation of the NLRP3 inflammasome, which is a multiprotein complex including NLRP3, ASC, and CASP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia can produce cytokines and chemokines that induce astrogliosis, which is a hallmark of neuroinflammation. [ 17 ] Consequently, the proinflammatory mediators could induce a vicious inflammatory cycle, causing neuronal cell dysfunction and death in the brain constantly. [ 18,19 ] Meanwhile, in the central nervous system (CNS), inflammation occurring and progressing can be mediated via activation of the NLRP3 inflammasome, which is a multiprotein complex including NLRP3, ASC, and CASP1.…”
Section: Discussionmentioning
confidence: 99%
“…Assembly and activation of the NLRP3 inflammasome could result in the generation of activated caspase‐1, and then initiate maturation and secretion of IL‐1β. [ 17 ] Evidence suggests that deficiency of NLRP3 and ASC could decrease Aβ plaque deposition and reduce microglial inflammatory activation both in vitro and in vivo. [ 20 ] Therefore, targeting the NLRP3 inflammasome associated neuroinflammation is an efficient way for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Besides, inhibition of inflammation during ischaemic stroke contributes to reduce ischaemic infarction. 24,30,41 Based on this evidence, we further in- 20 Ma et al demonstrated that rhTrx-1 exerts an antioxidative effect against neurological dysfunction and cerebral infarction. 21 Unlike these studies, we provided a new mechanism by which rhTrx-1 acted as an inhibitor of RIPK1 to reduce cerebral ischaemic injury, and we found inhibition of microglia RIPK1 reduced neuronal apoptosis ( Figure 6).…”
Section: F I G U R Ementioning
confidence: 72%
“…ROS accumulation was able to activate the NLRP3 inflammasome, and the activated NLRP3 inflammasome subsequently mediated neuroinflammation during ischaemic stroke by secretion IL‐1β. Deficiency of NLRP3 significantly alleviated neuroinflammation in ischaemic stroke and ischaemic injury 41 . It has been reported that RIPK1 can trigger the activation of the NLRP3 inflammasome by disrupting the mitochondrial membrane integrity and by promoting the release of ROS, which further promotes the production and secretion of IL‐1β to the extracellular space and initiates neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The Nod-like receptor protein 3 (NLRP3) inflammasome has been demonstrated to be crucial for the regulation of microglia-mediated neuroinflammation. 8,9 It consists of a cytosolic multiprotein complex, composed of NLRP3, apoptosis-associated speck-like protein (ASC), and procaspase-1, and can be activated by a wide range of exogenous and endogenous stimuli. 10 The activation of the NLRP3 inflammasome involves a two-step process.…”
Section: Introductionmentioning
confidence: 99%